Determinants of TFP in the fisheries sector of 28 coastal provinces in Vietnam - Duc, Nguyen Cao; Thuy, Ha Thi Thu; Phuong, Pham Thi Thu; Hung, Le Van; Trung, Nguyen Ngoc (Business: Theory and Practice, 2022)
This study uses annual data of The Enterprise Survey and Provincial Competitiveness Index to analyze determinants of TFP of the fisheries sector and fishery firms in 28 coastal provinces of Vietnam. The paper evaluated the effects of different institutional variables on TFP at the firm level. In addition, impacts of macro variables on sector’s TFP were also analyzed using sector aggregated TFP. Analyses of the study show that the industry’s macro environment and firm characteristics significantly affect the fisheries sector’s productivity. At the macro level, the more transparent the environment is, the higher the TFP. Thus, it is suggested that the local authorities of the coastal provinces of Vietnam need to speed up their reforms in administrative procedures, creating a favorable business environment for firms. At the micro-level, the variable of firm size is positively correlated with the TFP in the fisheries sector. The larger the size of the firm, the higher the productivity. In a labor-intensive industry such as fisheries, productivity increases with labor, indicating a low science and technology application level. To increase the sector’s productivity, state support to expand the application of advanced technologies for domestic firms is essential.